2007
DOI: 10.1108/03090560710773372
|View full text |Cite
|
Sign up to set email alerts
|

Personal characteristics, trust, conflict, and effectiveness in marketing/sales working relationships

Abstract: Purpose − The primary objective of this research is to test a model examining interpersonal trust between marketing managers and R&D managers during new product development projects. In this study we conceptualise interpersonal trust as a bidimensional construct with cognitive and affective components. Our integrative structural model specifies Weber's (1924) structural/bureaucratic dimensions − formalisation and centralisation to predict three communication dimensions, communication frequency, quality, and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 128 publications
(243 reference statements)
2
65
0
1
Order By: Relevance
“…Shrum et al (2001) examined 53 collaborations in physics and related sciences and found that trust was inversely associated with conflict. Another study (Massey and Dawes, 2007) based on data in 53 firms in Australia found that trust was negatively related with the dysfunctional interpersonal conflict between marketing and sales managers. Likewise, Porter and Lilly (1996) found that trust reduced work-related conflict in the project teams.…”
Section: The Link Between Trust In Peers and Conflictmentioning
confidence: 99%
“…Shrum et al (2001) examined 53 collaborations in physics and related sciences and found that trust was inversely associated with conflict. Another study (Massey and Dawes, 2007) based on data in 53 firms in Australia found that trust was negatively related with the dysfunctional interpersonal conflict between marketing and sales managers. Likewise, Porter and Lilly (1996) found that trust reduced work-related conflict in the project teams.…”
Section: The Link Between Trust In Peers and Conflictmentioning
confidence: 99%
“…Discussions by sales management experts lead to a conclusion that salesman who always prioritizes experience as an essential ingredient in any sales activity will tend to behave and work smarter (Massey and Dawes, 2007).…”
Section: Sales Experiencementioning
confidence: 99%
“…In other word, good trust condition will lead to less dysfunctional conflict. (Graham R. Massey & Philip L. Dawes, 2007) The influence of organizational trust on performance is always a popular research topic. The relationship between distributors and suppliers will be affected by organizational trust to a great extent.…”
Section: Trustmentioning
confidence: 99%
“…(Graham R. Massey & Philip L. Dawes, 2007) We want to focus on the effect of psychological distance and personal relationship on conflict, satisfaction and performance. Besides, we also use organizational trust to make this study more objective.…”
Section: Hypothesesmentioning
confidence: 99%